Investigation of a spread-spectrum protocol for local-area networks with asymmetric offered loads - Le, Hai Nam; O'Farrell, Timothy; Lockmann, S.; Takahashi, Kenzo; Finnish International Development Agency (FINNIDA) Finland (Bangkok : Asian Institute of Technology, 1993)
The research presented in this thesis consists of the investigation of a channel sensing spread spectrum with overload detection (CSSS/OD) protocol, and its general class, the channel load sense capability (CLSS/OD), under asymmetric offered load for use in optical fiber LANs. The mulliuser interference of a code division multiple access (CDMA) channel is taken into account in this research. Firstly, the analysis model of the CSSS/OD protocol (O'FARRELL, 1993) for symmetric load is modified to evaluate the perforn1ance of this protocol under asymmetric load conditions. Then both protocols are investigated by discrete event simulation. The simulation models are built up using OPNET/M version 2.3 which is a workstation-based network simulation tool. Finally, the delay/throughput perforn1ance of the CSSS/OD and CLSS/OD protocols are evaluated and compared with that of the ALOHA Spread-Spectrum (ALOHA-SS) and the Fiber Distributed Data Interface (FDDI) protocols under the same load conditions. The results demonstrate the robustness of the CDMA techniques when embedded in high-level protocols (e.g., ALOHA-SS, CSSS/OD and CLSS/OD) under asymmetric load conditions. Also the performance of CSSS/OD (& CLSS/OD) show a better delay/throughput characteristics over that of FDDI under both symmetric and asymmetric load conditions, thus making these protocols ideally suited to High-Speed Local Area Network applications.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Local area networks (Computer networks); Fiber optics